The Implementation of Cooperative Learning to Enhance the Creativity and Learning Outcomes of Ninth-Grade Students in Islamic Religious Education (PAI) at SMP Negeri 4 Brebes - Lulu Rahma Detriska; Didi Nur Hilal; Zahrotun Nisa; Annisa Anggraeni; Ati Umi Atun Nur Azizah; Dewi Rizqiah; Nur Kholidin (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
This study aims to analyze the implementation of the Cooperative Learning method in enhancing the creativity and learning outcomes of ninth-grade students in Islamic Religious Education (PAI) at SMP Negeri 4 Brebes, as well as to identify the supporting and inhibiting factors that influence its implementation. This study employed a qualitative approach with a case study design. Data were collected through observations, interviews, and documentation involving an Islamic Religious Education teacher and ninth-grade students. The findings reveal that the implementation of Cooperative Learning was carried out through three main stages: planning, implementation, and evaluation. The novelty of this study lies in its simultaneous analysis of the impact of Cooperative Learning on students’ creativity and learning outcomes in Islamic Religious Education, while also identifying contextual factors that influence its effectiveness at the junior secondary school level.